Comparison of the Pros and Cons of pH-Responsive Systems for Oral Insulin Delivery: A Concise Review (Tikrit Journal of Pharmaceutical Sciences, 2026)
Oral drug delivery is regarded as the most favored method of treatment due to its elevated patient compliance and reduced invasiveness. The oral route of administration of therapeutic proteins such as vaccines, antigens and hormones (insulin), compared to other routes, requires delivery systems that can overcome glitches in therapeutic proteins optimal utilization such as extensive first-pass hepatic metabolism, destruction in the gastrointestinal tract, large molecule size and poor penetration. Therefore, pH-responsive carriers for the delivery of insulin orally are regarded to be one of the most promising options. Insulin is now available in parenteral dose form, which can be administered mainly by subcutaneous injections. Subcutaneous administration method is linked with a number of complications that might impair patients' compliance. Oral administration of insulin is not currently feasible due to a number of problems that are associated with the structure of insulin and the architecture of the gastrointestinal system. Insulin is a peptide that, when oral administration occurs, has a tendency to be rendered inactive through the process of destruction that is accomplished by the enzymes and acids of the stomach. Therefore, the pH-responsive carriers make an effort to bypass the stomach. This allows for insulin release and subsequent absorption in its unaltered form within the intestine by aid of absorption enhancers. This review will discuss the progress made in the field of pH-responsive systems, with a particular focus on oral insulin delivery. It provides a comprehensive comparison of pH-responsive systems with other delivery systems from various aspects, such as formulation, insulin loading, and large-scale manufacturing, as well as the future prospects for oral insulin delivery. It also discusses the challenges that may be faced in scaling up production and offers our perspective on the clinical translation of in vitro findings into commercial products.